Affective disorders and chronic inflammatory conditions: analysis of 1.5 million participants in Our Future Health - Daniel J Smith; Katie F M Marwick; Arish Mudra Rakshasa-Loots; Duncan Swiffen; Christina Steyn (BMJ Mental Health)
Background Chronic inflammation is associated with psychiatric disorders. If inflammation is linked mechanistically to mental health, people living with chronic inflammatory conditions may experience mental health issues at higher rates than others.Objective To test this hypothesis, we analysed data from 1 563 155 adults living in the UK within the newly launched UK-wide Our Future Health research cohort.Methods Participants were split between two groups: people with self-reported lifetime diagnoses of six autoimmune conditions (n=37 808) and those without these diagnoses (n=1 525 347).Findings Lifetime prevalence (95% CI) of self-reported lifetime diagnoses of any affective disorder (depression, bipolar disorder, anxiety) was significantly higher (p<0.001) among people with autoimmune conditions (28.8% (28.4% to 29.3%)) than in the general population (17.9% (17.8% to 18.0%)), with similar trends observed for individual affective disorders. Prevalence of current depressive symptoms (9-item Patient Health Questionnaire (PHQ-9) ≥10, 18.6% vs 10.5%) and current anxiety symptoms (7-item Generalised Anxiety Disorder Scale (GAD-7) ≥8, 19.9% vs 12.9%) was also higher among people with autoimmune conditions. Odds of experiencing affective disorders, calculated using logistic regression models, were significantly higher in this group compared with the general population (OR (95% CI) = 1.86 (1.82 to 1.90), p<0.001), and these odds remained elevated when adjusting for the effects of age, sex, ethnicity (OR=1.75 (1.71 to 1.79), p<0.001) and additionally, for household income, parental history of affective disorders, chronic pain status and frequency of social interactions (OR=1.48 (1.44 to 1.52), p<0.001).Conclusions Overall, the risk of affective disorders among people living with autoimmune conditions was nearly twice that of the general population.Clinical implications Although the observational design of this study does not allow for direct inference of causal mechanisms, this analysis of a large national dataset suggests that chronic exposure to systemic inflammation may be linked to a greater risk for affective disorders. Future work should seek to investigate potential causal mechanisms for these associations.